PENGARUH JUMLAH PASIEN BPJS KESEHATAN TERHADAP PENDAPATAN RUMAH SAKIT UMUM DAERAH dr. ABDUL RIVAI KABUPATEN BERAU - Lisa, Purwaningsih (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2018)
The purpose of research that is done is to find how the influence of the number of patients health BPJS against earnings RSUD Dr. Abdul Rivai Berau district . While it is expected that writer of function as well as are the result of this research is to be able to used to apply a theory that obtained to in a situation indeed that is in the field and as material information for the hospital side about the influence of the number of patients health bpjs against RSUD Dr. Abdul Rivai Berau district. Based on the results of regression analysis shows that the number of patients health bpjs influence give a positive response to income of the hospital RSUD Dr. Abdul Rivai Berau district .Thus the more patients bpjs of health the more it income of the district general hospital RSUD Dr. Abdul Rivai Berau district that can be accepted .The results of the analysis that a change in the number of patients correlation BPJS health is affecting income of the hospital dr. abdul rivai so that rise or the decline of patients Dr. Abdul Rivai will have the effect of large exposure to income rsud dr. abdul rivai berau district. Hypothesis accepted , it is because based on the t generate that t count & gt; t table but it only increases the number of patients health BPJS significantly affect the income RSUD Dr. Abdul Rivai Berau district .